Fuzzy Inference System untuk Menentukan Tingkat Kompetensi Kepribadian Guru - Mawaddah Isfa Apriliyani; Hindayati Mustafidah; Dwi Aryanto (JUITA : Jurnal Informatika, 2012)
Teacher’s role is very important in school because they who will give the lessons to their students. Therefore, ateacherwhowillteachin theschools shouldhave the competencies, especially in personality competency. This research is belonged to Fuzzy Inference System with Tsukamoto method for determining the competency based on the teacher’s personality with a web base. In Tsukamoto method each consequent to the rules in the form of IF-THEN should be represented by a set of fuzzy with monotone membership function. The output inference of each rule is given explicitly (crisp) based on α-predicate (fire strength). The end result is obtained by using weighted average.Fuzzy data used is score data or value of personality competence. The rating score with scale A means (very good), B means (fair), C means (less good). Each personality competence component mentioned is used as figuration rule data by producing 243 rules. These rules are used to find µ-score in each variable that has been determined to find z score